The Impact of Banking Decision Support Systems in Improving Decision-Making in Commercial Banks (Field study on private banks in Lattakia Governorate) (Journal of Hama University, 2026)
The study aimed to determine the impact of banking decision support systems in improving the quality of marketing decisions. The researcher relied on the deductive approach as a general research method and followed the survey methodology. The research sample consisted of 151 individuals from the staff of commercial banks. The researcher then conducted a field study to demonstrate this relationship. The study concluded that banking decision support systems, banking information systems, and banking operational information systems have a role in improving the quality of banking marketing decisions in private commercial banks. The study recommended that banks should increase their interest in banking decision support systems because they will achieve quality in banking marketing decisions by achieving profits using fewer resources and providing services at lower costs..
Keywords: Key words: Banking decision support systems, banking information systems, banking operational information systems, quality of banking marketing decisions.